REFLEKSI NALAR FIKIH SOSIAL DALAM KRISIS LINGKUNGAN HIDUP - Nurul Huda (Al Maqashidi : Jurnal Hukum Islam Nusantara, 2021)
Social Fiqh based on paradigm that solve a social problem is the most important attention from syariah, so, the social fiqh must be corelated to social problem solving and the public basic requirements fulfillment, not only dharuriyah, hajiyah but also tahsiniyah. Ecology crisis is result from developmentalisme program only based on economic growth. The programs are investment, green revolution, and family planning. The social fiqh doesn't understand that the programs have strong relation, so, only ecology crisis or damaging environment is forbiden but the others aren't forbiden. Finally, the social fiqh and the government united to created imbalance in social order. Where is the maslahah spirit?